Предмет: Алгебра,
автор: ivanved1999
упростить выражение 5х-(4х-(3х-(2х-(х-1))))
Ответы
Автор ответа:
0
5х-(4х-(3х-(2х-(х-1))))=
5x-(4x-(3x-(2x-x+1)))=
5x-(4x-(3x-(x+1)))=
5x-(4x-(3x-x-1))=
5x-(4x-(2x-1))=
5x-(4x-2x+1)=
5x-(2x+1)=
5x-2x-1=
3x-1=
3x=1
x=1/3
если перед скобкай стоит " - " то знаки меняются на противо положнае
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Английский язык,
автор: maksim080630
Предмет: Биология,
автор: Настя424
Предмет: Химия,
автор: Igorchelus